Speaking Difficulties in EFL Learners: A Descriptive Study of Linguistic and Psychological Issues - Nurmadina HS; Luana Sasabone; Yuliah Yuliah; Musdalifah Djamaluddin; Nur Sapta Riskiawati (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2026)
Speaking is one of the most essential yet challenging skills in English as a Foreign Language (EFL) learning. This study aims to identify speaking difficulties experienced by EFL learners, focusing on linguistic, psychological, and learning-related issues. A quantitative descriptive research design was employed in this study. The participants were 16 undergraduate students from an English Department at a private university in Indonesia. Data were collected using a structured questionnaire consisting of 12 closed-ended items and analyzed using descriptive statistics, including frequencies and percentages. The findings reveal that students experienced various speaking difficulties, with linguistic problems emerging as the most dominant factors. Vocabulary limitation was identified as the primary issue, reported by all participants, followed by difficulties in distinguishing similar sounds, sentence construction, forming expressions, comprehension, pronunciation, and intonation. In addition, psychological factors were also reported as barriers to students’ speaking performance. Fear of making mistakes and lack of confidence were among the most prominent psychological issues, while anxiety and shyness were reported at lower levels. Furthermore, lack of motivation was found as an important learning-related factor affecting students’ engagement in speaking activities. This study concludes that speaking difficulties in EFL learners are multifaceted, involving linguistic competence, psychological conditions, and learning-related factors. The findings suggest that effective speaking instruction should address both language proficiency and learners’ affective needs to enhance speaking performance.